An Observational Study of Parents Reading a Storybook About Bullying to Their Young Child: Are Bystander Responses Discussed? - Green, Vanessa A.; Jacobsen-Grocott, Tessa; Salmivalli, Christina; Wilson, Marc (WILEY, 2026)
In the context of bullying the developmental progression of how and why most children remain as passive bystanders is unclear. Early socialization practices such as how parents read storybooks that depict bullying to their young children may be a contributing factor. Structured video-recorded observations of 97 parent-child dyads (85 mothers) (M age of children = 37.9 m) were conducted in participants' own homes. Participants were instructed to read a specifically adapted book that included child and adult witnesses, and the repetition of inappropriate-but developmentally typical-preschool behavior. Of the 1767 comments made by the parents (that were not part of the story script), 614 referred to the moral messages conveyed in the story; however, only nine of these comments were bystander-related and were made by five parents. One parent made suggestions about what a witness could do to help the victim. There were no statistically significant relationships between the likelihood of parents highlighting bullying/bystander behaviour and their own experiences of child/adolescent bullying. The findings from this study suggest that children may be inadvertently socialized into passive bystanding behaviour when witnessing bullying because defending behaviours are not typically taught to young children. This omission may be considered as a type of silent socialization.